On uncertainties in simulations in engineering design: A statistical tolerance analysis application. (May 2014) - Walter, Michael; Storch, Markus; Wartzack, Sandro
Simulations not only facilitate new and unprecedented insights in highly sophisticated science areas, but also support product design in engineering in terms of improved functionality, cost and time issues. However, as a matter of fact, simulations examine limited excerpts of real systems with accompanying simplifications, abstractions and idealizations. Hence, there is a distinct need to be aware of upcoming risks in simulation outcomes caused by uncertainties. These influence every step of forward-thinking simulation design which is not only restrained by modeling practice but begins with reality perception itself. The intention of the paper is to embed an awareness of uncertainty in the context of simulation by linking major classes of uncertainty with uncertainties within simulations in engineering design. Besides the decisive inclusion of reality as the starting point, mathematic approaches are also used to understand how those uncertainty classes evolve through exponential knowledge creation of systems. The transfer to statistical tolerance analysis shall finally put emphasis on the practical classification of uncertainty, starting from data preparation via concept design and mathematical implementation to result depiction. In the end, the reader's conception of possible uncertainties in special simulation cases shall be sharpened which, vice versa, shall lead to even better and well-thought-out simulation outcomes.